(untitled) (Journal of Universal Science Research, 2025)
The article discusses key conceptions related to influence of pragmatic aspects on the process of translation. Ignorance of pragmatic principles may undermine the overall adequacy of the target text and lead to misunderstanding or incorrect reconstruction of the author’s ideas in translation.